PENGARUH PENAIKKAN MINAT BERBELANJA KONSUMEN DI TOKOPEDIA SELAMA MASA PANDEMI - Dalimunthe, Rodiah; Aslami, Nuri (LPPM Universitas Labuhanbatu, 2021)
Journal writing and the research conducted aims to identify, analyze and determine how the effect of enhancing the shopping interest of consumers in India during the pandemic. The research method used is quantitative descriptive research methods. The data collection technique used is the technique of questionnaire or questionnaires distributed in the form of g-form online with respondents as many as 30 people are divided over women 20 people and men 10 people as well as with engineering interview online through electronic media with 2 speakers are selected at random. The results of the survey and online interviews were analyzed and interpreted in a narrative. The results showed that the increased interest for consumers on both in India during the period of the pandemic is influenced by the price, ease of transaction, the level of confidence, the ad as well as attractive promotions offered with many payment systems that can be selected.